2017
DOI: 10.1016/j.omtn.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The Bioactivity of D-/L-Isonucleoside- and 2′-Deoxyinosine-Incorporated Aptamer AS1411s Including DNA Replication/MicroRNA Expression

Abstract: In this study, chemical modification of 2′-deoxyinosine (2′-dI) and D-/L-isothymidine (D-/L-isoT) was performed on AS1411. They could promote the nucleotide-protein interaction by changing the local conformation. Twenty modified sequences were obtained, FCL-I and FCL-II showed the most noticeable activity improvement. They stabilized the G-quadruplex, remained highly resistant to serum degradation and specificity for nucleolin, further inhibited tumor cell growth, exhibited a stronger ability to influence the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 63 publications
0
9
1
Order By: Relevance
“…The obtained K D values for the binding interaction between the free AS1411 aptamer and the AS1411-C 8 complex with nucleolin were 8.63 pM and 6.38 pM, respectively. The obtained K D values are lower than those reported in the literature, being potentially overestimated by the use of labelled oligonucleotides or the use of a different peptide than that used in those studies 28,29 . Nonetheless, both values are in the same range, being slightly lower in the case of the aptamer-ligand complex which suggests that the ligand does not negatively affect the recognition of the protein by the aptamer.
Figure 8Saturation binding plots fitted to Michaelis-Menten model.
…”
Section: Resultscontrasting
confidence: 74%
“…The obtained K D values for the binding interaction between the free AS1411 aptamer and the AS1411-C 8 complex with nucleolin were 8.63 pM and 6.38 pM, respectively. The obtained K D values are lower than those reported in the literature, being potentially overestimated by the use of labelled oligonucleotides or the use of a different peptide than that used in those studies 28,29 . Nonetheless, both values are in the same range, being slightly lower in the case of the aptamer-ligand complex which suggests that the ligand does not negatively affect the recognition of the protein by the aptamer.
Figure 8Saturation binding plots fitted to Michaelis-Menten model.
…”
Section: Resultscontrasting
confidence: 74%
“…Multiple mapping and functional studies have revealed important roles of G-quadruplex structures in the regulation of gene expression and transcription, protein translation and proteolysis, DNA repair, maintenance of the stability of chromosome ends, and epigenetic regulation [2,3,4,5,6,7]. For now, many selective G-quadruplex ligands show potential for antitumor therapy applications by causing DNA damage responses and growth arrest in human cancer cells [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…G-quadruplex (G4) was first discovered by Gellert et al In 1962, G-quadruplex is composed of DNA or RNA strands rich in serially repeated guanine (G) [ 39 ] induced by metal ions, and under certain ionic strength and appropriate pH conditions, It is a special secondary structure of nucleic acid formed by the accumulation of tetrad structure formed by Hoogsteen hydrogen bond [ 40 ], and it is also the supra-molecular structure of G-rich nucleic acid [ 41 44 ]. Advances in the chemical and structural biology of G-quadruplex have enabled the design of specific G4 aptamers to be used as novel anticancer agents and suitable for clinical trials [ 45 ].…”
Section: Dna Rich In G Basesmentioning
confidence: 99%